Using near‐field coupled circularly polarised antennas as frequency‐independent variable phase shifters. Issue 11 (1st May 2014) - Sipal, V.; Narbudowicz, A.; Ammann, M.J.
Abstract : A novel concept of frequency‐independent variable phase shifters is introduced. It is based on the use of circularly polarised (CP) antennas coupled in the near‐field. For transmission between two CP antennas in the far‐field, a rotation around the boresight axis produces a phase change in the transfer function. This concept is exploited and validated also for near‐field coupling between two CP antennas. Therefore, two close‐coupled CP antennas can act as an adjustable phase shifter with the phase shift controlled by the angle between the structures. The bandwidth depends on the CP bandwidth of the antenna. This concept is valuable for future phase shifters in millimetre‐wave applications where rotation can be facilitated by MEMS elements.